2021
DOI: 10.1002/sctm.20-0455
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Adipose-Derived Stem Cells Mitigate Acute Radiation Syndrome by the Rescue of Damaged Bone Marrow Cells from Apoptosis

Abstract: Acute radiation syndrome (ARS) is the radiation toxicity that can affect the hematopoietic, gastrointestinal, and nervous systems upon accidental radiation exposure within a short time. Currently, there are no effective and safe approaches to treat mass population exposure to ARS. Our study aimed to evaluate the therapeutic potential of allogeneic adipose-derived stem cells (ASCs) for total body irradiation (TBI)-induced ARS and understand the underlying mitigation mechanism. We employed 9.25 Gy TBI dose to C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…h-ARS not only damages HSPCs, but also adversely affects the BM's stromal cell and ECM [ 20 ]. To treat h-ARS, we developed a biomimetic BM microniches in vitro that recapitulated the porous structure and stiffness of the natural BM matrix, orchestrated with primary HSPCs and MSCs co-culture, to replace the irradiated BM through BM cavity administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…h-ARS not only damages HSPCs, but also adversely affects the BM's stromal cell and ECM [ 20 ]. To treat h-ARS, we developed a biomimetic BM microniches in vitro that recapitulated the porous structure and stiffness of the natural BM matrix, orchestrated with primary HSPCs and MSCs co-culture, to replace the irradiated BM through BM cavity administration.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unique 3D and porous structure, natural BM niche encompasses versatile supporting cells, such as MSCs, adipocytes, osteocytes, and endothelial cells which contribute to the maintenance of HSCs and HSPCs [ 19 ]. HSPCs and MSCs are the major stem cell sources for cell-based therapy that have shown good efficacy in ameliorating h-ARS [ 20 ]. MSCs niche supports hematopoiesis in the BM while facilitate HSPCs proliferation under allogeneic microenvironments [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to mTOR, the ERK signaling pathway plays a crucial role in proliferation and adipogenesis. Xiaomin Ning et al, in their publication, posit that adipogenesis is activated by ERK signaling [ 58 ]. Since we observed that metformin inhibited adipogenesis and proliferation, we decided to investigate the effect of metformin on ERK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of adipose precursor cells was performed as follows [ 31 ]. Adipose tissue biopsies obtained after surgical procedures were aseptically transferred to the laboratory in sterile sealed tubes.…”
Section: Methodsmentioning
confidence: 99%